2012
DOI: 10.1021/ic3020805
|View full text |Cite
|
Sign up to set email alerts
|

Quintuple Bond Reactivity toward Group 16 and 17 Elements: Addition vs Insertion

Abstract: The low valent, coordinatively unsaturated, and formally quintuply bonded bimetallic aminopyridinato chromium complex 1 was investigated regarding its reactivity toward group 16 and 17 elements. Reaction of 1 with O(2) yielded a dimeric Cr oxo complex 2, a compound with a high formal oxidation state carrying both bridging and terminal oxo ligands. Reactions with the higher homologues of the group lead to the formation of dimeric Cr(II) complexes in which E(2)(2-) ligands were formed [E = S (3), Se (4), and Te … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…X-ray crystallographic analysis on 12a and 12b revealed the temperature-dependent molecular motion. In light of the remarkable reactivity of the type II quintuplebonded compounds, [33,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] the characterization of 5-11 bodes well for a systematic reactivity study of these medium-coordinate univalent dichromium complexes. Selected bond lengths (Å) and angles ( ): 12a: Cr(1)-Cr (2), 1.8261 (5); N(1)-Cr(1)-N(4), 127.26 (10); N(5)-Cr(1)-N(1), 119.65 (10); N(4)-Cr (1)-N(5), 109.26 (10); N(2)-Cr(2)-N (3), 127.85 (10); N(3)-Cr(2)-N(6), 110.46 (10); N(2)-Cr(2)-N(6), 118.21 (10).…”
Section: Discussionmentioning
confidence: 99%
“…X-ray crystallographic analysis on 12a and 12b revealed the temperature-dependent molecular motion. In light of the remarkable reactivity of the type II quintuplebonded compounds, [33,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] the characterization of 5-11 bodes well for a systematic reactivity study of these medium-coordinate univalent dichromium complexes. Selected bond lengths (Å) and angles ( ): 12a: Cr(1)-Cr (2), 1.8261 (5); N(1)-Cr(1)-N(4), 127.26 (10); N(5)-Cr(1)-N(1), 119.65 (10); N(4)-Cr (1)-N(5), 109.26 (10); N(2)-Cr(2)-N (3), 127.85 (10); N(3)-Cr(2)-N(6), 110.46 (10); N(2)-Cr(2)-N(6), 118.21 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these compounds, such as [18] or {R 2 Cr(μ-η 2 ) (Ch 2 )CrR 2 } (R 2 = substituted terphenyle) [19], include amines that appear to be too bulky for further reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[7] These low-coordinate quintuple-bonded species not only have interesting metal-metal bonding, but also show remarkable reaction chemistry. [8][9][10][11][12][13][14][15][16] Recent studies have indicated that there are strong analogies between the d component of the metal-metal quintuple bonds and the p component of the carbon-carbon multiple bonds. For example, the quintuple bonded molybdenum amidinate dimers [Mo 2 {m-k 2 -RC(N-2,6-iPr 2 C 6 H 3 ) 2 } 2 ] (R = H (1), Ph) [17] react with two equivalents of terminal alkynes to give the first aromatics containing two multiple-bonded dimetal units by a [2+2+2] cycloaddition process, [14] while its chromium analogue [Cr 2 {m-k 2 -HC(N-2,6-iPr 2 C 6 H 3 ) 2 } 2 ] (2) [18] reacts with alkynes to afford [2+2] adducts.…”
mentioning
confidence: 99%
“…In addition, four septet signals corresponding to the four methine hydrogen atoms of eight iPr substituents suggest that the benzylidynes 8-10 feature an unsymmetrical molecular conformation. The 13 C NMR spec- troscopy show strongly deshielded resonance signals at d = 409.6 (8), 406.9 (9), and 398.8 ppm (10) corresponding to the bridgehead carbon atoms of the carbyne ligands. Such aroyl disproportionation also occurs to an alkyl acyl group.…”
mentioning
confidence: 99%
See 1 more Smart Citation